Liposome-trimethyl chitosan nanoparticles codeliver insulin and siVEGF to treat corneal alkali burns by inhibiting ferroptosis - Xiaojing Xiong; Huiting Jiang; Yukun Liao; Yangrui Du; Yu Zhang; Zhigang Wang; Minming Zheng; Zhiyu Du (Wiley, 2023)
Abstract Alkali burns are potentially blinding corneal injuries. Due to the lack of available effective therapies, the prognosis is poor. Thus, effective treatment methods for corneal alkali burns are urgently needed. Codelivery nanoparticles (NPs) with characteristics such as high bioavailability and few side effects have been considered effective therapeutic agents for ocular diseases. In this study, we designed a new combination therapy using liposomes and trimethyl chitosan (TMC) for the codelivery of insulin (INS) and vascular endothelial growth factor small interfering RNA (siVEGF) to treat alkali‐burned corneas. We describe the preparation and characterization of siVEGF‐TMC‐INS‐liposome (siVEGF‐TIL), drug release characteristics, intraocular tracing, pharmacodynamics, and biosafety. We found that siVEGF‐TIL could inhibit oxidative stress, inflammation, and the expression of VEGF in vitro and effectively maintained corneal transparency, accelerated epithelialization, and inhibited corneal neovascularization (CNV) in vivo. Morever, we found that the therapeutic mechanism of siVEGF‐TIL is possibly relevant to the inhibition of the ferroptosis signaling pathway by metabolomic analysis. In general, siVEGF‐TIL NPs could be a safe and effective therapy for corneal alkali burn.